ChemInform Abstract: Silver‐Catalyzed Meerwein Arylation: Intermolecular and Intramolecular Fluoroarylation of Styrenes. Issue 39 (September 2015) - Guo, Rui; Yang, Haodong; Tang, Pingping
Abstract The first example of a silver‐catalyzed intermolecular and intramolecular Meerwein fluoroarylation of styrenes with aryl diazonium salts under mild conditions is described.